2020
DOI: 10.53378/346028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Test Anxiety on Test Scores of Pre-service Teachers in Northern Cyprus

Abstract: A lot has been written with regards to the subject of anxiety and its role on influencing learning outcomes yet it seems the issue of anxiety is continuously debated by research and academic scholars. While teachers may think that issues of anxiety in education are either overhyped or overemphasized, learners think otherwise. To analyze the views of the preservice teacher on the concept of test anxiety especially on its influence on the academic performance of students, a mixed research design was adopted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…This analysis found evidence to show that the normal language teaching approach in SLA classrooms does not have a positive impact on language learners' communicative competence in this context. In line with the reasoning of similar studies (Ironsi, 2020;Ironsi & Popescu, 2021b), it can be concluded that the normal teaching approach does not improve learners' communicative competence contrary to the assumption of some studies (Diane, 2019;Sifakis, 2019;Schedlitzki, 2019;Tavoosy & Jelveh, 2019;Wilson et al, 2019). The results of the experiment clearly argue for the use of a different language teaching method that can inevitably improve language learners' communicative competence.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…This analysis found evidence to show that the normal language teaching approach in SLA classrooms does not have a positive impact on language learners' communicative competence in this context. In line with the reasoning of similar studies (Ironsi, 2020;Ironsi & Popescu, 2021b), it can be concluded that the normal teaching approach does not improve learners' communicative competence contrary to the assumption of some studies (Diane, 2019;Sifakis, 2019;Schedlitzki, 2019;Tavoosy & Jelveh, 2019;Wilson et al, 2019). The results of the experiment clearly argue for the use of a different language teaching method that can inevitably improve language learners' communicative competence.…”
Section: Discussionsupporting
confidence: 67%
“…During the lessons, learners are encouraged to participate, interact and use language meaningfully. These findings are in tandem with studies that support that appropriate method, language exercises, strategies and approaches must be used in a language classroom, they emphasize that these variables are essential for the success of teaching four language skills (Chang, 2019; Ironsi, 2020; Ironsi & Popescu, 2021b). Obviously, it is novel that students confirmed that this type of teaching improved their listening and speaking skills.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations